1998
DOI: 10.2337/diacare.21.11.1951
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma pancreastatin-like levels in gestational diabetes: correlation with catecholamine levels.

Abstract: Catecholamine and pancreastatin-like levels were found elevated in gestational diabetic subjects. These counterregulatory hormones may play a role in the insulin resistance syndrome of gestational diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 2 publications
1
19
0
3
Order By: Relevance
“…It seems the PLC-b3 isoform is specifically activated by pancreastatin receptors and mediated by Ga 11 [44]. Increased circulating pancreastatin concentrations have been found in patients with Type II diabetes [25], gestational diabetes [45] and in hypertensive patients [26]. These data suggest that pancreastatin could have a role in the insulin resistance syndrome.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…It seems the PLC-b3 isoform is specifically activated by pancreastatin receptors and mediated by Ga 11 [44]. Increased circulating pancreastatin concentrations have been found in patients with Type II diabetes [25], gestational diabetes [45] and in hypertensive patients [26]. These data suggest that pancreastatin could have a role in the insulin resistance syndrome.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, we have recently found that plasma pancreastatin-like immunorreactivity correlates with plasma norepinephrine in essential hypertension [28] and gestational diabetes [45]. Since insulin resistance and the sympathoadrenal system are involved in the metabolic abnormalities associated with hypertension [46] we proposed that pancreastatin might contribute to the counterregulatory effect of catecholamines in pathophysiological conditions, when catecholamines concentrations are increased.…”
Section: Discussionmentioning
confidence: 99%
“…Sánchez-Margalet és mtsai [26] a pancreastatin emelkedett szintjét fi gyelték meg gestatiós diabetesesekben kontrollegyénekhez képest. Ugyanebben a vizsgálatban pozitív korrelációt mutattak ki a pancrestatin és egyes katecholaminok (epinefrin és norepinefrin) szintje kö-zött.…”
Section: A Kromogranin-a éS Hasításából Keletkező Fehérjék Extracelluunclassified
“…A különböző endokrin szö-vetekben proteolitikus módosításokat követően alakul át extracellulárisan működő biológiailag aktív peptidformákká. A CgA-ból kialakuló fehérjék, mint a pancreastatin, a vasostatin, a WE-14 és további formák jelentős és specifi kus biológiai hatással rendelkeznek (1. táblázat) [26,27,28,29,30,34,35,45,47,48,49,50,51,52].…”
Section: Következtetésekunclassified
“…This hypothesis was substantiated by the data on the effect of PKC inhibition abrogating the inhibitory action of PST on insulin-stimulated tyrosine phosphorylation, PI3K activity, and GLUT4 translocation. Enhanced serine kinase activity has been described in insulin resistance (64), and PST may contribute to this pathophysiological feature along with other counterregulatory hormones, such as catecholamines, whose circulating levels correlate with those of PST (49)(50)(51).…”
Section: Pancreastatin Modulates Insulin Signalingmentioning
confidence: 99%